Determination the Relationship of Interleukin IL-17 to Peanut Allergy in Basrah Governorate - Mahjar, Nasrien Thamer; Raisan, Shayma`a Jabbar (University of Thi-Qar Journal of Science, 2022)
In this study Collected 90 samples (74 allergic patients and 16 samples healthy people), during the period from October 0202to January 0200 , with ages ranging from (20-65)years.The current study recorded an increased concentration of IgE in patients at a rate of 76.67% compared with healthy people samples, Also, this study showed an increase in Total IgE antibodies in peanut-allergic patients at a rate of 36.49%. The current study is shown that the females had the highest concentration of IgE antigen-specific to peanuts at a rate of (29.73%) compared with maleswith significant difference (p < 0.05). Moreover , this study recorded that fourth age group had the highest percentage (76.6%) for peanut-allergic compared to the other age groups with a significant difference between them (p< 0.05). In contrast, the results recorded a decrease in the concentration of interleukin IL-17A and IL-17F among those peanut-allergic patients.